2019
DOI: 10.4067/s0718-18762019000200106
|View full text |Cite
|
Sign up to set email alerts
|

Role of Privacy Legislations and Online Business Brand Image in Consumer Perceptions of Online Privacy Risk

Abstract: Developing an approach to manage privacy risk is critical to the success of e-marketing. Understanding the antecedents of privacy risk is therefore essential for the success of e-business. Because governments, businesses, and consumers are economic agents, this study examined the effects of governmental (privacy legislations) and firm-related (online business brand image) factors on consumer perceptions of online privacy risk. This paper proposes a conceptual model for exploring the underlying mechanisms of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
(87 reference statements)
2
8
0
Order By: Relevance
“…These findings are in line with many previous studies (e.g. Sharma et al, 2019;Wang & Wang, 2019), which have shown that the perceived value of social media crowdsourcing depends on the extent to which participants trust it.…”
Section: Theoretical Implicationssupporting
confidence: 93%
See 3 more Smart Citations
“…These findings are in line with many previous studies (e.g. Sharma et al, 2019;Wang & Wang, 2019), which have shown that the perceived value of social media crowdsourcing depends on the extent to which participants trust it.…”
Section: Theoretical Implicationssupporting
confidence: 93%
“…The literature (e.g. Sweta, 2014;Wang & Wang, 2019) confirms that the perceived value of social media crowdsourcing depends on the extent to which participants trust it. Rodr ıguez et al (2020) claims that honourable people will not continue as members of online communities, despite their positive intention, if they believe that other participants are opportunistic.…”
Section: Trust and The Perceived Value Of Social Media Crowdsourcingmentioning
confidence: 97%
See 2 more Smart Citations
“…This cluster primarily provides the theoretical basis for this field and may shed light on further research. For example, many studies propose an integrated theoretical framework to understand context-specific antecedents and outcomes of privacy concerns (e.g., [46][47][48][49][50][51][52]). An implication for further research is thus to exploit context and contextual differences in managing consumer privacy.…”
Section: Thematic Clusters In Consumer Privacy Researchmentioning
confidence: 99%